Conductive-network enhanced microwave absorption performance from carbon coated defect-rich Fe2O3 anchored on multi-wall carbon nanotubes. (December 2019) - Wang, Lei; Yu, Xuefeng; Li, Xiao; Zhang, Jie; Wang, Min; Che, Renchao
Abstract: Electron conduction capability plays an extremely important role in the field of electromagnetic wave energy conversion. Herein, a novel dual-conductive-network hybrid material was successfully synthesized, where carbon coated defecr-rich Fe2 O3 anchored on multi-wall carbon nanotubes (MWCNTs). The entangled MWCNTs serve as a carbon skeleton to support the porous Fe2 O3 particle, coating by the ligand-derived conductive carbon. Decorated carbon layer not only acts as a link to connect the Fe2 O3 and MWCNTs, but also furnish a new electronic transmission path. Related electromagnetic parameters and electron transportation behavior can be effectively adjusted and controlled via tuning carbon substrate content. Meanwhile, the typical defects and charge density distribution in this C@Fe2 O3 @MWCNTs system were proved by geometric phase analysis and electron holography technology. This ternary composite can be a potential excellent microwave absorber with a special conductive-netlike structure and multi-interface architecture, benefiting to the conductivity loss and interfacial polarization between porous Fe2 O3 microspheres with carbon materials. The optimal reflection value of microwave loss is −49.9 dB at 10.0 GHz with the absorber thickness of 2.0 mm. The as-prepared C@Fe2 O3 @MWCNTs composites exhibit high-performance microwave absorption and cater to the highly efficient attenuation capability, thin thickness, and lightweight requirements for modern microwave absorption materials. Graphical abstract: Carbon coated defect-rich Fe2 O3 anchored on multi-wall carbon nanotubes composites exhibited strong polarization loss and enhanced microwave absorption performance. Image 1